2019
DOI: 10.3389/fped.2019.00363
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Bacterial Overgrowth in Children: A State-Of-The-Art Review

Abstract: Small intestinal bacterial overgrowth (SIBO) is a heterogenous and poorly understood entity characterised by an excessive growth of select microorganisms within the small intestine. This excessive bacterial biomass, in turn, disrupts host physiology in a myriad of ways, leading to gastrointestinal and non-gastrointestinal symptoms and complications. SIBO is a common cause of non-specific gastrointestinal symptoms in children, such as chronic abdominal pain, abdominal distention, diarrhoea, and flatulence, amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 153 publications
0
79
0
8
Order By: Relevance
“…Consequently, probiotic intake may have a greater influence on the duodenal microbiota than on the distal gut microbiota [22]. Probiotics have also been used for treatment of small intestinal bacterial overgrowth in children [23]. Further studies on modulation of the duodenal microbiota for IM treatment through microbiota-modulating therapies, such as probiotics, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, probiotic intake may have a greater influence on the duodenal microbiota than on the distal gut microbiota [22]. Probiotics have also been used for treatment of small intestinal bacterial overgrowth in children [23]. Further studies on modulation of the duodenal microbiota for IM treatment through microbiota-modulating therapies, such as probiotics, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This gap of information is probably associated with difficulties to reach and sample this segment of the gastrointestinal tract 6 . However, SI microbiota alterations could lead to gastrointestinal and non‐gastrointestinal symptoms and complications 9 . Although there has been an important progress to understand the structure and function of the gut microbiota, there is still a need to further characterize this new organ, particularly in the SI.…”
Section: Introductionmentioning
confidence: 99%
“…IBS is a complicated disease that display comorbidities of both impairment of GI motility and CNS symptoms. The cause of SIBO in IBS is incompletely understood although several studies demonstrated that some of the indole producing bacteria like Escherichia coli exhibit high abundance in the small intestine of SIBO associated IBS patients (Ghoshal et al, 2014, Leite et al, 2020, Avelar Rodriguez et al, 2019. Our findings raise the possibility that SIBO leads to an increase of microbial tryptophan metabolite production in the small intestine, which then activates Trpa1+EECs to increases intestinal motility and modulate CNS activity through the vagal nerve, resulting in the complex comorbidities of intestinal and psychiatric disorders in IBS.…”
Section: Trpa1+eecs Are Frontline Intestinal Sensorsmentioning
confidence: 76%